2017
DOI: 10.1038/cddis.2017.541
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA profiling reveals an abundant circLMO7 that regulates myoblasts differentiation and survival by sponging miR-378a-3p

Abstract: Circular RNAs (circRNAs) have been identified from various tissues and species, but their regulatory functions during developmental processes are not well understood. We examined circRNA expression profiles of two developmental stages of bovine skeletal muscle (embryonic and adult musculus longissimus) to provide first insights into their potential involvement in bovine myogenesis. We identified 12 981 circRNAs and annotated them to the Bos taurus reference genome, including 530 circular intronic RNAs (ciRNAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(223 citation statements)
references
References 24 publications
14
209
0
Order By: Relevance
“…This results in the excess production of mitochondrial superoxide radicals and generates poor hepatic antioxidant defense systems [32]. Insulin signaling is the major pathway that controls glucose homeostasis by coordinating important metabolic processes, including glucose uptake, glycolysis, glucose oxidation, and glycogen synthesis in nearly all body tissues [56]. Previous studies have shown IUGR increases the mRNA levels of hepatic gluconeogenic genes and reduces the mRNA levels of insulin signaling genes in the liver [42].…”
Section: Discussionmentioning
confidence: 99%
“…This results in the excess production of mitochondrial superoxide radicals and generates poor hepatic antioxidant defense systems [32]. Insulin signaling is the major pathway that controls glucose homeostasis by coordinating important metabolic processes, including glucose uptake, glycolysis, glucose oxidation, and glycogen synthesis in nearly all body tissues [56]. Previous studies have shown IUGR increases the mRNA levels of hepatic gluconeogenic genes and reduces the mRNA levels of insulin signaling genes in the liver [42].…”
Section: Discussionmentioning
confidence: 99%
“…[95][96][97][98][99] Circ-ZNF609 promotes human myoblast proliferation through an unknown mechanism 95 ; however, circZfp609, which is the gene symbol of mouse ZNF609, sponges miR-194-5p to sequester its inhibition of BCL2-associated transcription factor 1 (BCLAF1) and repress myogenic differentiation by affecting the expression of Myf5 and MyoG. [95][96][97][98][99] Circ-ZNF609 promotes human myoblast proliferation through an unknown mechanism 95 ; however, circZfp609, which is the gene symbol of mouse ZNF609, sponges miR-194-5p to sequester its inhibition of BCL2-associated transcription factor 1 (BCLAF1) and repress myogenic differentiation by affecting the expression of Myf5 and MyoG.…”
Section: Muscle Developmentmentioning
confidence: 99%
“…[95][96][97][98][99] Circ-ZNF609 promotes human myoblast proliferation through an unknown mechanism 95 ; however, circZfp609, which is the gene symbol of mouse ZNF609, sponges miR-194-5p to sequester its inhibition of BCL2-associated transcription factor 1 (BCLAF1) and repress myogenic differentiation by affecting the expression of Myf5 and MyoG. 97,98 In addition, chicken circRBFOX2 promotes cell proliferation by enhancing the expression of cyclin D2 through sponging miR-206. It appears to function as a ceRNA for miR-378a-3p by targeting histone acetylation enzyme 4 (HDAC4).…”
Section: Muscle Developmentmentioning
confidence: 99%
“…Combining these approaches, multiple labs have now characterized circRNAs across multiple cells types and species, and within various developmental and disease states. One very recent example of this type of analysis is described by Chen and colleagues who compared circRNA in fetal and adult muscle cells (5). …”
Section: Recent Advances In Genomic Analyses Have Enabled Systemic Stmentioning
confidence: 99%
“…Many circRNAs described in Table 1 are proposed to work via titration of miRNAs. For example, Wei et al indicate that circLMO7 regulates myoblast differentiation and survival by sponging mir-378-3p (5). …”
Section: How Can Circrnas Affect Cell Function?mentioning
confidence: 99%